Aviação agrícola no Brasil: caracterização, invisibilização e debates - Mhereb, Gabriel de Araujo (2017)
The aerial spraying of pesticides, carried out mainly by the agricultural aviation sector in Brazil, is defended by part of society as a fundamental technology for contemporary agricultural crops to increase production; on the other hand, institutions, researchers, NGOs and social movements related to the field and health are opposed to its use, due to its high hazard and to the accidents recorded, thus proposing its prohibition. From the controversy involving aerial spraying establishment, this study aims to develop a context and a characterization of the agricultural aviation sector in Brazil, going back to the modernization of the field and the emergence of agricultural aviation; it also presents a characterization of this sector based on available information on the area that is served, the evolution of the fleet and the accidents recorded. It will also be analyzed the main informational systems on poisoning by pesticides in Brazil, the data on intoxication related to the set of pesticides, as well as the instruments of information collection, focusing on the investigation/evaluation sheets used for the notification of human intoxication, investigating the existing bottlenecks in data collection involving the aerial spraying of pesticides. Public manifestations caused by agricultural aviation will be exposed, identified and subdivided by different social fields: the scientific field, the field of social movements and the media field. The results show that the agricultural aviation sector is expanding in Brazil, due to the increasing in the fleet of airplanes, service providers distributed throughout the country and also in the sprayed area. It is shown that agricultural aviation has considerably higher accident rates than other civil aviation segments. There is also a limitation in the form of registration of the official information and in the records presented by the organizations of the sector and also by the notification systems of intoxications. Through the manifestations reported, it was demonstrated that despite the absence of official data, there is an expressive set of reports of institutions and people living and/or working in rural and urban environments on the impacts of this sector.